Unilateral Emissions Mitigation, Spillovers, and Global Learning - CHATTERJI, Shurojit (Institutional Knowledge at Singapore Management University, 2014)
What's the role of unilateral measures in global climate change mitigation in a post-Durban, post 2012 global policy regime? We argue that under conditions of preference heterogeneity, unilateral emissions mitigation at a subnational level may exist even when a nation is unwilling to commit to emission cuts. We establish that under certain assumptions, in a global strongly connected network of countries, learning the costs of switching to a low emissions activity can result in a universal adoption of such activities. We analyze the features of a policy proposal that could accelerate convergence to a low carbon world in the presence of global learning.